Römisches Strafrecht. Theodor Mommsen. - Mommsen, Theodor, 1817-1903 (Cambridge library collection. Classics., 2012)
Römisches Strafrecht was first published in 1899 and complements Mommsen's earlier, monumental study of Roman constitutional law. Applying the same historical method, he attributes the evolution of criminal law to the demise of the Roman Republic. The book, here reissued in two volumes, is divided into five main sections. The first discusses the nature of criminal law. Mommsen next looks at the institutions involved in administering criminal law, and the roles of different officials within them. He identifies three types of trial: trial by magistrate alone, trial by magistrate and comitia, and trial by jury, and describes their stages from the courtroom process to the pronouncement of sentence.